Emergent modular neural control drives coordinated motor actions - Lemke, Stefan M.; Ramanathan, Dhakshin S.; Guo, Ling; Won, Seok Joon; Ganguly, Karunesh (Nature neuroscience, 2019)
A remarkable feature of motor control is the ability to coordinate movements across distinct body parts into a consistent, skilled action. To reach and grasp an object, ‘gross’ arm and ‘fine’ dexterous movements must be coordinated as a single action. How the nervous system achieves this coordination is currently unknown. One possibility is that, with training, gross and fine movements are co-optimized to produce a coordinated action; alternatively, gross and fine movements may be modularly refined to function together. To address this question, we recorded neural activity in the primary motor cortex and dorsolateral striatum during reach-to-grasp skill learning in rats. During learning, the refinement of fine and gross movements was behaviorally and neurally dissociable. Furthermore, inactivation of the primary motor cortex and dorsolateral striatum had distinct effects on skilled fine and gross movements. Our results indicate that skilled movement coordination is achieved through emergent modular neural control. Different body parts must be coordinated to perform skills. Lemke et al. report that distinct patterns of brain activity emerge during learning related to each body part and conclude that such patterns are refined independently yet function together.